Effect of pre-harvest fruit bagging on post-harvest quality of guava cv. Swarupkathi - Rahman, Md Mizanur; Hossain, Md Mokter; Rahim, Md Abdur; Rubel, Md Humayun Kabir; Islam, Md Zahurul (Fundamental and Applied Agriculture, 2018)
The investigation was carried out at Germplasm Centre (BAU–GPC), Bangladesh Agricultural University, during March to July 2016 in order to investigate the effect of pre-harvest fruit bagging on post-harvest quality of guava cv. Swarupkathi. Four different bagging materials viz. brown paper bag, white paper bag, white polythene bag, and black polythene bag were included for the study and uncovered fruits were used as control treatment. The experiment was laid out in a randomized complete block design with three replications. Fruit bagging treatments showed significant effects on different parameters studied. It was observed that fruit size, fruit weight, vitamin C concentration, and moisture content increased due to fruit bag- ging. Fruits gained the maximum in size (6.59 cm length, 5.86 cm diameter) and weight (164.26 g) under white paper bag followed by white polythene bag (131.3 g). The skin color of fruits was very attractive in case of white paper bag than that of other treatments. Total soluble solid concentration of the fruit was found to be the maximum (12.33% Brix) under brown paper bag while the maximum vitamin C concentration (162.14 mg 100 g−1) was recorded under white paper bag. Uncovered fruits showed the maximum total sugar, non-reducing sugar, and reducing sugar concentrations (10.13%, 6.05%, 4.08%, respectively). The results also revealed that fruit bagging in general, improved the growth and quality of guava fruits as compared to the control (no bagging). Among the various fruit covering materials, white paper bag was found to be the best for overall improvement of physical and chemical quality of guava cv. Swarupkathi.